(untitled) (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2022)
One of the catfish production centers in Palembang City is located in Srimulya Village, Sematang Borang District. Srimulya Village is planned to be confirmed as a Fisheries Area in Palembang City. This study aims to analyze the level of technical efficiency, price efficiency and economic efficiency of catfish cultivators, Srimulya Village, Sematang Borang District, Palembang City. This research was conducted in September 2022. Sampling was carried out using proportional random sampling technique with a total of 30 respondents. The data used include primary data and secondary data. Data were analyzed descriptively qualitatively and descriptively quantitatively. Researchers used qualitative methods, namely by analyzing the characteristics of each respondent. Technical efficiency were analyzed using Frontier 4.1 software. The results showed level of technical, allocative and economic efficiency of catfish farming business in Srimulya Village, Sematang Borang District, Palembang is in an inefficient condition. Based on the technical efficiency criteria, if the efficiency value is 0.91 (<1), it means that the allocation of the use of production inputs exceeds the efficiency value so that the use of production inputs must be reduced. Allocative efficiency (price) of 1.87 (>1) means that it is inefficient in terms of price. Judging from the value of the economic efficiency of the business of 1.70 (> 1), it means that the catfish farming business is not yet economically efficient.